Against Teleology in the Study of Race: Toward the Abolition of the Progress Paradigm. (December 2018) - Seamster, Louise; Ray, Victor
We argue that claims of racial progress rest upon untenable teleological assumptions founded in Enlightenment discourse. We examine the theoretical and methodological focus on progress and its historical roots. We argue research should examine the concrete mechanisms that produce racial stability and change, and we offer three alternative frameworks for interpreting longitudinal racial data and phenomena. The first sees racism as a "fundamental cause, " arguing that race remains a "master category" of social differentiation. The second builds on Glenn's "settler colonialism as structure" framework to describe race relations as a mutually constituted and place-based system of resource allocation. The third framework draws attention to racialized agency.